Fabrication and Characterisation of Titanium Dioxide (TiO2) with Different Synthesis Temperatures for Solar Cell Applications - Siti Kudnie, Sahari; ANDRE ANDING, TEDONG; Muhammad, Kashif; Abdul Rahman, Kram; Marini, Sawawi; Hasanah, Lilik; Kuryati, Kipli; Lee Chin, Kho (Academy of Sciences Malaysia, 2023)
In this investigation, the effects of various synthesis temperatures of titanium dioxide (TiO₂) on the structural, optical, and electrical properties of Dye-Sensitised Solar Cell (DSSC) were investigated. As an organic dye for DSSC, Beetroot plant was chosen. The TiO₂ solution was prepared using the sol-gel method and deposited on glass using the spin coating technique. Several compounds, including absolute ethanol, Titanium Isopropoxide (TTIP), Glacial Acetic Acid (GAA), Triton X-100, and deionised water, were combined to create the TiO₂ solution. Using a Scanning Electron Microscope (SEM), an Ultraviolet-Visible (UV-Vis) spectrometer, and a Keithely 2450 Sourcemeter, the structural, optical, and electrical properties of TiO₂ were determined. The results indicate that the TiO2 thin film synthesised at a temperature of 60°C has the most porous structure and the smallest particle size when compared to others. This temperature also produces TiO₂ with the sharpest peak absorption of 0.40 at a wavelength of 575.50 nm, resulting in a bandgap energy of 3.10 eV. Furthermore, it has a higher Field factor (FF) value that results in the highest energy conversion efficiency, ɳ of 0.34 %.